2021
DOI: 10.3389/fgene.2021.778715
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Model of Tumor-Infiltrating B Lymphocyte Specific RNA-Binding Protein-Related Genes With Potential Prognostic Value and Therapeutic Targets in Multiple Myeloma

Abstract: Background: RNA-binding proteins (RBPs) act as important regulators in the progression of tumors. However, their role in the tumorigenesis and prognostic assessment in multiple myeloma (MM), a B-cell hematological cancer, remains elusive. Thus, the current study was designed to explore a novel prognostic B-cell-specific RBP signature and the underlying molecular mechanisms.Methods: Data used in the current study were obtained from the Gene Expression Omnibus (GEO) database. Significantly upregulated RBPs in B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…unveiled that ADAR expression was negatively associated with immune cell infiltration. 158 The oncogenic role of ADAR1 was also identified by Shi et al., who confirmed that ADAR1 by regulating Rho GTPase splicing can aid the progression of a rare subtype of non‐Hodgkin's lymphoma, the so‐called ocular adnexal B‐cell lymphoma. 159 …”
Section: Implications Of Non‐m 6 a Rna Modificatio...mentioning
confidence: 80%
See 1 more Smart Citation
“…unveiled that ADAR expression was negatively associated with immune cell infiltration. 158 The oncogenic role of ADAR1 was also identified by Shi et al., who confirmed that ADAR1 by regulating Rho GTPase splicing can aid the progression of a rare subtype of non‐Hodgkin's lymphoma, the so‐called ocular adnexal B‐cell lymphoma. 159 …”
Section: Implications Of Non‐m 6 a Rna Modificatio...mentioning
confidence: 80%
“…Single‐sample Gene Set Enrichment Analysis conducted by Zhang et al. unveiled that ADAR expression was negatively associated with immune cell infiltration 158 . The oncogenic role of ADAR1 was also identified by Shi et al., who confirmed that ADAR1 by regulating Rho GTPase splicing can aid the progression of a rare subtype of non‐Hodgkin's lymphoma, the so‐called ocular adnexal B‐cell lymphoma 159 …”
Section: Implications Of Non‐m6a Rna Modification In Haematological O...mentioning
confidence: 95%